Association between Vitamin D Supplementation and Mental Health in Healthy Adults: A Systematic Review - Dominika Guzek (MDPI AG, 2021)
Vitamin D is considered to be a crucial factor that influences symptoms of depression, negative emotions, and quality of life, but to date, no systematic review has been conducted with regard to its effect on other domains of mental health. The aim of the study was to evaluate the influence of vitamin D supplementation on mental health in healthy adults. The systematic review was registered in the PROSPERO database (CRD42020155779) and performed according to the PRISMA guidelines. The literature search was conducted in PubMed and Web of Science databases and included intervention studies published until October 2019. The human studies were included if the supplementation regimen involved the administration of a specified dosage of vitamin D to an adult sample. A total of 7613 records were screened and assessed independently by two researchers, based on their title, abstract, and full text sequentially. Finally, 14 studies were included, and their risk of bias was assessed using the Newcastle–Ottawa Scale (NOS). The studies were included if they presented the results of various doses of vitamin D, compared the supplementation results with the placebo effect, compared the outcome with no supplementation, or observed effect of specific dose applied. The assessed mental health outcomes mainly included depressive symptoms, or depression, well-being, quality of life, mood, general mental component, and anxiety, but single studies also included other parameters such as distress, impression of improvement, and fear of falling and flourishing. The results of the majority of studies did not confirm a positive influence of vitamin D supplementation. None of the high-quality studies (assessed using NOS), which evaluated outcomes other than depression, supported the hypothesis that vitamin D supplementation effectively ameliorates mental health issues, while they present conflicting evidence for depression. Some studies indicated that supplementation should be combined with physical activity to provide effective results, and that supplementation is less effective than vitamin D supply from food sources. The included studies were conducted in diverse populations and followed various doses and intervals of administration, so the results may be incomparable, which should be considered as a limitation. The conducted systematic review did not provide strong evidence for a positive effect of vitamin D supplementation on mental health in healthy adults.